2015
DOI: 10.1186/s12937-016-0192-7
|View full text |Cite
|
Sign up to set email alerts
|

Effect of vitamin D3 supplementation on iron status: a randomized, double-blind, placebo-controlled trial among ethnic minorities living in Norway

Abstract: BackgroundBoth vitamin D and iron deficiencies are widespread globally, and a relationship between these deficiencies has been suggested. However, there is a paucity of randomised controlled trials assessing the effect of vitamin D supplementation on iron status.PurposeWe aimed to investigate whether 16 weeks of daily vitamin D3 supplementation had an effect on serum ferritin, haemoglobin, serum iron and transferrin saturation.MethodsOverall, 251 participants from South Asia, Middle East and Africa aged 18–50 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
28
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(34 citation statements)
references
References 40 publications
6
28
0
Order By: Relevance
“…Cholecalciferol was the main form of vitamin D that were supplemented in these studies. The duration of supplementation with vitamin D also varied from 3 h to 6 months [40][41][42][43][44][45][46][47][48][49][50][51][52][53].…”
Section: Study Characteristicsmentioning
confidence: 99%
See 1 more Smart Citation
“…Cholecalciferol was the main form of vitamin D that were supplemented in these studies. The duration of supplementation with vitamin D also varied from 3 h to 6 months [40][41][42][43][44][45][46][47][48][49][50][51][52][53].…”
Section: Study Characteristicsmentioning
confidence: 99%
“…Different types of vitamin D were used in these studies, four studies received vitamin D fortified food with cholecalciferol [40,[46][47][48], eight studies received oral vitamin D (cholecalciferol) supplements [42,44,45,[49][50][51][52][53] and in one study subjects were supplemented with ergocalciferol and another one with calcitriol [41,43]. The minimum vitamin D dosage was 20 IU and maximum was 500,000 IU according to these studies ( Table 1).…”
Section: Intervention Characteristicsmentioning
confidence: 99%
“…This is consistent with several studies in chronic kidney disease, cardiovascular disease, and the general population, which have described a positive association between vitamin D status and hemoglobin and/or an inverse association between vitamin D status and anemia (913, 15, 39, 40). Data from clinical trials have been mixed (3942), but recent studies in CKD and critically ill adult patient populations found that treatment with vitamin D or its analogues resulted in significant increases in hemoglobin concentrations (24, 43). This association has not been previously studied in IBD animal models or clinical studies.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore,vitamin D deficiency may affect the regulation ofhepcidin, which could accelerate the decrease in haemoglobinand increase the incidence of anaemia (Zughaier et al, 2014). Iron deficiency anaemia is the last end stage of progressionfrom normal iron status to frank deficiency (Madar et al, 2016).…”
Section: Fig 2 Correlation Between Maternal 25-oh (D) and Corresponmentioning
confidence: 99%